2020
DOI: 10.21203/rs.3.rs-53608/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trends of Interventional Radiology procedures during the Covid-19 pandemic: The first 27 weeks in the eye of the storm

Abstract: ObjectivesWhile the Novel Coronavirus (COVID-19) pandemic looks to persist, institutions promote delaying procedures. Understanding trends and demands of interventional radiology (IR) procedures in the infected and COVID-free populations are needed in long-term planning. We detail IR procedure trends in the first 27 weeks of the pandemic and compare with the pre-pandemic era. MethodsIn this IRB approved retrospective electronic case review, all IR patients in our institution from 1 January to 9 July 2020, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…The decline in non-COVID-19-related healthcare services resulted in a 50-70% reduction in medical imaging [7]. Studies have shown pandemic-related reductions or cancellations in interventional radiology procedures by 29-43% [8][9][10][11][12]. COVID-19-related stressors have impacted the mental health of physicians.…”
Section: Chickmentioning
confidence: 99%
“…The decline in non-COVID-19-related healthcare services resulted in a 50-70% reduction in medical imaging [7]. Studies have shown pandemic-related reductions or cancellations in interventional radiology procedures by 29-43% [8][9][10][11][12]. COVID-19-related stressors have impacted the mental health of physicians.…”
Section: Chickmentioning
confidence: 99%